PENINGKATAN KEMAMPUAN GURU DALAM PENYUSUNAN RPP BERBASIS HOTS MELALUI SUPERVISI AKADEMIK KEPALA SEKOLAH DI SMAN 1 PARDASUKA KABUPATEN PRINGSEWU - Zainal, Zainal (LPPM STKIP PGRI Bandar Lampung, 2019)
Based on observations and supervision by the author of teachers at SMAN 1 Pardasuka, Pringsewu Regency, it was found that Teacher Competence in preparing lesson plans based HOTS was still low. The objective of this research is to describe the improvement of teacher skills in preparing lesson plans based HOTS through the academic supervision of the principal, this research method was Classroom Action Research. The object of this research is the teacher's behavior in preparing the lesson plans by applying the verb operational group (Higher Order Tihinking Skills (HOTS)) on the objectives and evaluation of lesson plans. Research procedures in this research including planning, action, observation and reflection. This research consisted of two cycles with two meetings. The research subjects consisted of 36 teachers at SMA Negeri 1 Pardasuka Pringsewu. Research data were collected using observation sheets. Data were analyzed using percentages. The results of the study in the first cycle, there were 24 teachers who got good ratings with the achievement data of 74.79. In cycle II there were very good achievements totaling 21 teachers and 13 other teachers got good ratings as well as two high-level teachers there was quite an increase to a good level from a sufficient ranking of 12 people who were previously in the first cycle. Based on the results of research that had been done, it can be concluded that Academic supervision of school principals can improve Teacher Competence in preparing Lesson Plans based HOTS at SMAN 1 Pardasuka Pringsewu Regency.